Corrections to “Graphene-Metamaterial Based Tunable Broadband Polarization Insensitive Absorber for Terahertz Antenna Design” - Rummanur Rahad; Abu S. M. Mohsin; Mohammed Belal Hossain Bhuian; Md. Mosaddequr Rahman (IEEE Access)
Presents corrections to the paper, (Corrections to “Graphene-Metamaterial Based Tunable Broadband Polarization Insensitive Absorber for Terahertz Antenna Design”).